Acceptance Of Website-Based Learning Media with Independent Flow in Elementary Schools in Sumedang Regency - Ariyanti Ariyanti; Yunus Abidin; Mila Mandiyani; Iim Siti Karimah; Yadi Suryadi (CV. Ksatria Siliwangi, 2025)
In the current digital era, the integration of information and communication technology in education has become an urgent necessity. One rapidly developing innovation is the use of website-based learning media. This study examines the acceptability of website-based learning media designed in alignment with the Merdeka learning framework in elementary schools in the Sumedang region. The research employs a quantitative approach, using a correlational survey method with path analysis. The findings indicate that, among the ten evaluated indicators, two indicators Social Influence on Behavioral Intention and Effort Expectancy on Behavioral Intention play a decisive role in determining the acceptability of instructional materials and media. These indicators demonstrate a strong positive influence on the developed media, indicating high levels of acceptance. The results show that social influence and perceived ease of use are the primary determinants of acceptance and effectiveness of the learning media.